Corporality as an attribute of sculpture (European context) - R. M. Rusin (Ukrainian Cultural Studies, 2017)
The historical development of art is a change of paradigms. Each paradigm contains a special understanding of art, defined bothby the act of creativity itself and by the evaluation of its results. It is especially important to identify the origins of these changes, identify their stages, and determine the direction of the evolution of artistic creativity. In this context, corporeality as an artistic paradigm of European sculpture is considered in an article in the historical dimension from classics to postmodernism. Background research driven by changes that have suffered over the past century art not only in terms of formative principles, but also in terms of being a work of art. The term "art" is not given a priori; it is inseparable from the historical conditions of its own realization and filled with different content. In ancient tradition, from which theoretical understanding of art originates, provides an understanding of art as mimetic activity. For plastic art of the ancient Greeks man was the epitome of all things, the prototype of all creation and the created. The human body in great shape was almost the only model of art aesthetic. The Greeks thought it only as a stature completeness. For the Greeks, body language was the language of soul, although Greek plastics did not know what analysis characters the cult of the individual, which is typical for the art of modern times. Plasticity, the ancient body kinetics can be regarded as some elements of the semantic structure of a particular language as a kind of mimicry. Plastic modern European sculpture shows opposite to the ancient classics, Christian traditional relationship of mind and body. Antiquity knew dualism of mind and body, and provided perception of the gods only in the body incarnation. Christianity brought a legislated dualism and brought early naive monism attitude into the historically natural decay. In the art of the Renaissance in Europe, due to rethinking of ancient Christian tradition, experience acquires the tendency of forming an image of ideal body oriented on classic examples. In the mid-nineteenth century, under the influence of a new understanding of human corporeality was an appeal to antiquity qualitatively new level due to the growing trend of "naturalization" in human culture and criticism concerning the previous historical periods. In the culture of the twentieth century, there was a quite relevant anthropological stance of negativism. Justification of individual values has led to a lack of uniform standards, because it was perceived as an encroachment on personality. The natural beauty in all its perfection, the image of which was the purpose and content of Antiquity plastics and the Renaissance art lost all its worthiness and has become a subject of neglecting within the postmodernism.